Augmented Reality Technologies In Education - Mamadjanova Svetlana Valentinovna (Genius Journals, 2023)
This article is devoted to the topic of using augmented reality in education. It describes the benefits of using AR technology in the learning process, including better memorization, the ability to create interactive learning materials, and the ability to explore different places and cultures without leaving the classroom. Some disadvantages of using augmented reality in education are also given.
Keywords: immersive learning; augmented reality; education; interactivity